The Federal Democratic Republic of Ethiopia : Poverty Reduction Strategy Paper Annual Progress Report. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2004)
This report assesses the Annual Progress Report on the implementation of the Sustainable Development and Poverty Reduction Program (SDPRP), which is the Poverty Reduction Strategy Paper for Ethiopia. It reviews the fundamental development objectives of the SDPRP to build a free-market economic system in the country, which will enable the economy to develop rapidly, to end dependence on food aid, and to allow poor people to benefit from economic growth. It also assesses the challenges and prospects in the SDPRP continued implementation.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet